Structural Rigging of Lignin Precursors for Customized Porous and Graphene‐Like Carbons towards Enhanced Supercapacitive Performance in Aqueous and Non‐Aqueous Electrolytes. Issue 15 (13th August 2019) - Liu, Mingren; Zhang, Kejing; Si, Mengying; Yu, Hongbo; Chai, Liyuan; Shi, Yan
Abstract: Maximum supercapacitive performance in different electrolytes is desirable in the design of advanced carbon materials but still challenged by the conflicting properties of electrolytes. Herein, a practical and scalable strategy to customize carbon materials for aqueous and non‐aqueous electrolytes was proposed via structural rigging of lignin precursors. The resultant graphene‐like hierarchical porous carbon sheets from low‐molecular‐weight lignin exhibit a high electrical conductivity of 17.8 S cm −1, a prominent capacitance of 245 F g −1 at 1 A g −1 and impressive chemical stability in the symmetric supercapacitor of ionic liquid electrolyte. The top‐level energy density of 96.7 Wh kg −1 at a power density of 0.9 kW kg −1 and 48.5 Wh kg −1 at 20.5 kW kg −1 is also obtained. In contrast, the 3D oriented N/O co‐doped porous carbon composed of high‐molecular‐weight lignin possesses high specific surface area (>2400 m 2  g −1 ), regulated micropores and rich heteroatoms for remarkable specific capacitances of 402 F g −1 and 306 F g −1 at 1.0 A g −1 in three‐ and two‐electrode configurations of aqueous electrolyte, respectively. The established formation mechanisms further extend the exploration of highly plastic lignin precursors for diverse energy storage systems. Abstract : Rigged lignin : Matching of electrodes and electrolytes is confined by the conflicting properties of diverse electrolytes. Now, a practical and scalable strategy to customize carbon materials for aqueous and non‐aqueous electrolytes is demonstrated by the structural rigging of lignin precursors